Implementasi Perda Nomor 8 Tahun 2015 Tentang UMKM Di Kabupaten Serang Dalam Pengembangan Kerajinan Gerabah Di Desa Bumi Jaya Kecamatan Ciruas - Rizki Amilia; Abdul Hamid; Rd Nia Kania Kurniawati (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2021)
This study discusses the Implementation of Regional Regulation No. 8 of 2015 concerning SMEs in Serang Regency in the Development of Pottery Crafts in Bumi Jaya Village, Ciruas District. The purpose of this study was to determine the implementation efforts made by the Serang District Government through the Department of Cooperatives, Industry and Trade for micro pottery businesses in Desa Bumi Jaya, Ciruas District. This research uses a descriptive method with a qualitative approach. Determination of informants in this study using purposive sampling technique. Data collection techniques are done through observation, direct interviews and documentation. Testing the validity of the data in this study was carried out by triangulating data sources and member checks associated with the theory of public policy implementation Van Metter & Van Horn, Deddy Mulyadi 2016. Which consists of six indicators namely policy standards and targets, resources, communication between organizations and strengthening activists, implementing agent characteristics, socio-economic and political conditions, and implementor disposition. The data analysis technique uses the concept proposed by Miles and Hubberman. The results showed that the effort to implement Perda Number 8 of 2015 concerning MSMEs in Serang Regency in the Development of Pottery Crafts in Bumi Jaya Village, Ciruas District was still not optimal. This refers to the implementation efforts made by the Department of Cooperatives, Industry and Trade of Serang Regency which are still nature thorough in and are more oriented to routine government work. These conditions ultimately hindered the process of implementation for pottery artisans in Desa Bumi Jaya. The researcher recommends that the Department of Industry and Trade Cooperatives of Serang Regency to provide assistance in the form of capital for each pottery SME group in Bumi Jaya Village for the implementation of the perda, has integrity to the MSME pottery actors in Bumi Jaya Village to more intensely provide an understanding of based marketing ways e-commerce to improve better product competitiveness by making existing earthenware vessels in Bumi Jaya Village become icons or landmarks in Serang Regency that prioritize the potential of the region and provide new innovations that will increase the knowledge of the craftsmen to technology literacy